The Effect of Self Efficacy, Emotional Intelligence, and Entrepreneurial Motivation on Entrepreneurship Interest: Case Study of FEBI UINSU Students - Agung, Muhammad; Marliyah, Marliyah; Aisyah, Siti (Business Education Program of Universitas Pendidikan Indonesia, 2024)
This research aims to determine the influence of Self Efficacy, Emotional Intelligence, and Entrepreneurial Motivation on the Entrepreneurship Interest of FEBI UINSU Students, both partially and simultaneously. This research approach is associative. The population was FEBI UINSU students, totaling 4.523 and the sample was 100 FEBI UINSU Stambuk 2020 and 2021 students. Data collection techniques in this research used interview techniques, documentation studies, observations and questionnaires. The data analysis technique in this research uses Multiple Linear Regression Analysis Test, Hypothesis Test (tTest and F Test), and Coefficient of Determination. Data processing in this research used the SPSS (Statistical Package for the Social Sciences) software program version 29.00. Partially, the Self- Efficacy variable has a significant effect on Entrepreneurial Interest. Partially, the Emotional Intelligence variable has a significant effect on Entrepreneurial Interest. Partially, the Entrepreneurial Motivation variable has a significant effect on Entrepreneurial Interest. Simultaneously, the variables Self-Efficacy, Emotional Intelligence and Entrepreneurial Motivation have a significant effect on Entrepreneurial Interest.